A antecipação de tutela na ação civil pública ambiental - Guetta, Mauricio (2012)
The scope of this paper is to analyze the injunction in public civil suits aiming the protection of an ecologically balanced environment. In the first chapter, issues related to the effectiveness of material protection of the environment will be described, since necessary to the fully comprehension of the central theme of this thesis. Accordingly, considerations will be drawn on environmental protection in the Constitution of 1988, the characteristics of the environmental good, the guiding principles of the effectiveness of environmental protection, environmental damage, liability and environmental forms of compensation for damage to the right of all to a balanced environment and/or to the environment itself. Following this overview of the material rights object to this analysis, the theme of injunction as an instrument to the effectiveness of the environmental protection will be dealt. Initially, the paper will evaluate the Microsystem of Collective Lawsuits, the access to justice under a collective prism, the effectiveness of the collective environmental lawsuit and jurisdictional cognition, and further the classification, adopted on this paper, of injunction as a type of a differentiated jurisdictional protection. Based on these premises, this paper proceeds to construe the legal statutes of injunction in environmental public civil suits, analyzing the concept and legal nature of the institute, the statutes applicable, the relation between judicial protection of satisfaction and injunction natures and the prerequisites for the concession of injunction protection in collective lawsuits. We further describe the application of injunction, the limits of the court when assessing the anticipatory request, the moment of the upholding decision, the possibility of revocation and modification of the decision that upholds or denies the injunction, the hypothesis of irreversibility of the upholding decision and liabilities resulting from improper handling of the injunction instrument. This paper will also verify how the injunction is applied in the different types of jurisdictional decisions, declaratory, constitutive and condemnatory, as well as the instruments for its application, the bill of review appeal as the correct procedural instrument to the revision of the injunction and injunction against the State, and the necessary abiding to the motivation principle. Finally, once analyzed the themes we understand necessary to the full comprehension of injunctions in environmental civil public suits, we will conclude describing our findings